Parental presence and intranasal dexmedetomidine for the prevention of anxiety during anesthesia induction in children undergoing tonsillectomy and/or adenoidectomy surgery: A randomized controlled trial - Yao, Jing; Gong, Hesong; Zhao, Xiaochun; Peng, Qinxue; Zhao, Hongjuan; Yu, Shuangshuang (Frontiers in Pharmacology, 2022)
Background: During the perioperative period of pediatric surgery, it is extremely stressful for the children and parents to enter operating room and receive the anesthesia induction. The study was designed to evaluate the perioperative outcomes with parental presence at induction of anesthesia (PPIA), intranasal dexmedetomidine and combination usage of PPIA and intranasal dexmedetomidine . Methods: In this prospective study, 124 children were randomly divided into four groups: Control group:(no parental presence and intranasal dexmedetomidine ),PPIA group:(Parental presence), DEX group( intranasal dexmedetomidine (1.0 μg/kg)), PPIA+DEX group:(parental presence and intranasal dexmedetomidine (1.0 μg/kg)). Anxiety of children was the primary outcome,evaluated by Modified Yale Preoperative Anxiety Scale-Short Form (mYPAS-SF). Secondary outcomes included:Induction Compliance Checklist (ICC); Paediatric anesthesia Emergence Delirium scale (PAED); The COMFORT Behavior scale (The COMFORT-B scale); State-Trait Anxiety Inventory (STAI);Visual analog scale(VAS). Results: Children in PPIA+DEX group exhibited significantly lower mYPAS-SF score and ICC score compared with all three other groups (P<0.001),and children in PPIA+DEX group exhibited significantly lower mYPAS-SF score ICC score compared with PPIA group and DEX group (P <0.05).Children’s PAED score in PPIA group，DEX group，PPIA + DEX group were significantlyr than Control group(P<0.001).The STAI-S scores of PPIA group, DEX group, and PPIA+DEX group were significantly lower than score of group Control(P<0.001).The VAS scores of PPIA group, DEX group, and PPIA+DEX group were significantly higher than score of Control group.(P <0.001),and the score of PPIA+DEX group was significantly higher than those of PPIA group and DEX group(P <0.05). Conclusions: The combination usage of PPIA and intranasal dexmedetomidine is more effective than PPIA or intranasal dexmedetomidine for alleviating preoperative anxiety of children ,improving children’s induction compliance and parental satisfaction.